Identification and Pathogenicity of Escherichia coli from Cloacal Swabs - Arie Khoiriyah; Sumardi Sumardi; Hendri Busman (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
Colibacillosisis is an infectious disease in poultry caused by pathogenic Escherichia coli (E. coli) as primary or secondary agents. This study were aim to identify and test the pathogenicity ofE. coli isolated from chicken cloacal swabs. The samples used in this study were E. coli isolated from chicken cloacal swabs as many as 42 samples. The first stage in this research was subculturing E.coli in Eosin Methylene Blue Agar (EMBA) medium, then identified by Gram stain and biochemistry with Triple Sugar Iron Agar (TSIA), Sulfide Indole Motility (SIM), Simmons Citrate Agar (SCA) and Methyl Red Voges-Proskauer (MRVP). Pathogenicity of E. coli was tested by culturing in Blood Agar to see the results of hemolysin production and on Sorbitol-MacConkey Agar (SMAC) to see the ability of Sorbitol fermentation. The results obtained were 12 isolates was pathogenic E. coli looked from the results of the pathogenicity test in the Blood Agar and SMAC Agar.